(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The use of mechanical energy in daily life including industries and transport applications are increasing rapidly. Induction motor has special advantages because of less cost, reliable, robust and less maintenance when compared to other motors. It also has special features which satisfies all the requirements. On the whole 3-phase IM (Induction motor) plays major role in several applications (i.e. industrial, mechanical). The meticulous behavior of induction motor modeling and speed control can aid for controlling of machine application where flawless results can be obtained. The major faults in the IM effect the air gap flux, where the mathematical modeling can helpful to estimating the errors obtain while designing the motor. The paper represents the bit by bit implementation of 3-phase induction motor modeling and speed control using MATLAB simulation.